Snow Cover as a Factor of Growth of Annual Tree Rings under Contrasting Environmental Conditions of the West Siberian Plain - N. I. Bykov; A. A. Shigimaga; N. V. Rygalova (Лëд и снег, 2023)
The results of the analysis of the relationship between the width of annual tree rings of various woody plants and snow cover characteristics are presented: the dates of setting-up and destruction (loss) of stable snow cover, the duration of its existence, the thickness and water content of snow cover for the period of maximum snow accumulation. The studied areas are the forest-tundra zone, the northern taiga subzone, the southern forest-steppe subzone, and the dry steppe subzone within boundaries of the West Siberian Plain. Data from observations of snow cover on routes and meteorological sites of Roshydromet for 1966–2020 (for forest tundra and northern taiga) and 1966–2018 (for forest-steppe and dry steppe) together with dendrochronological samples obtained by the authors in these natural zones and subzones were used for this study. It was found that the thickness and water content of the snow cover play greater role for the radial growth of trees in the forest-tundra and dry steppe as compared to the northern taiga and southern forest-steppe. In the dry steppe, the trees of the upper parts of the low ridges and flat interfluves (plakors) are more sensitive to these snow cover characteristics, while in the forest-tundra this is important for the lower parts of the slopes. The dates of destruction of stable snow cover are more significant in the southern regions than in the northern ones. In the southern forest-steppe, the early loss of the snow cover increases the rate of growth of tree rings, while in the dry steppe it weakens it. The dates of setting-up of the stable snow cover are more important for the growth of trees compared to the dates of its loss, especially in the forest-tundra and southern forest-steppe since the later it starts, the greater the growth of trees. Importance of the duration of the period with stable snow cover for tree growth is higher in the southern regions. Its increasing in the southern forest-steppe reduces the growth of trees but increases in the dry steppe.